Genome-Wide Identification and Expression Profiling of Germin-Like Proteins Reveal Their Role in Regulating Abiotic Stress Response in Potato - Zaynab, Madiha; Peng, Jiaofeng; Sharif, Yasir; Fatima, Mahpara; Albaqami, Mohammed; Al-Yahyai, Rashid; Khan, Khalid Ali; Alotaibi, Saqer S.; Alaraidh, Ibrahim A.; Shaikhaldein, Hassan O.; Li, Shuangfei (Frontiers in Plant Science, 2022)
Germin and germin-like proteins (GLPs) perform a significant role in plants against biotic and abiotic stress. To understand the role of GLPs in potato a comprehensive genome-wide analysis was performed in potato genome. The current study identified a total of 70 StGLPs genes in the potato genome, distributed among 11 chromosomes. Phylogenetic analysis exhibited that StGLPs were categorized into six groups with high bootstrap values. StGLPs gene structure and motifs analysis showed a relatively well-maintained intron-exon and motif formation within the cognate group. Additionally, several cis-elements in the promoter regions of GLPs were hormones and stress-responsive and different families of miRNAs target StGLPs. Gene duplication under selection pressure also exhibited positive and purifying selections in StGLPs. In our results, the StGLP5 gene showed the highest expression in response to salt stress among all expressed StGLPs. Total 19 StGLPs genes were expressed in response to heat stress. Moreover, three genes, StGLP30, StGLP17, and StGLP14, exhibited a relatively higher expression level in the potato after heat treatment. Total 22 genes expressed in response to abscisic acid (ABA) treatment indicated that ABA performed an essential role in the plant defense or tolerance mechanism to environmental stress. RNA-Seq data validated by RT-qPCR also confirm that the StGLP5 gene showed maximum expression among selected genes under salt stress. Concisely, our results provide a platform for further functional exploration of the StGLPs against salt and heat stress conditions.